2005
DOI: 10.1021/ic050808q
|View full text |Cite
|
Sign up to set email alerts
|

((Fluoroformyl)imido)sulfuryl Difluoride, FC(O)NS(O)F2:  Structural, Conformational, and Configurational Properties in the Gaseous and Condensed Phases

Abstract: Structural, conformational, and configurational properties of the gaseous molecule ((fluoroformyl)imido)sulfuryl difluoride, FC(O)N=S(O)F(2), have been studied by vibrational spectroscopy (IR (gas) and Raman (liquid)) and quantum chemical calculations (HF, MP2, and B3LYP with 6-31+G* and 6-311+G* basis sets); in addition, the solid-state structure has been determined by X-ray crystallography. FC(O)N=S(O)F(2) exists in the gas phase as a mixture of a favored antiperiplanar-synperiplanar form (the S=O double bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The characteristic bands centered at 1446 and 1277 cm -1 in the IR spectrum of the gas phase and at 1437 and 1272 cm -1 in the Raman spectrum of the liquid phase are straightforwardly assigned to the antisymmetric and symmetric NSO stretching modes, respectively, in fair agreement with the data reported for the related molecules FSO 2 NS(O)F 2 , NCNS(O)F 2 , and FCONS(O)F 2 . The band assigned to the NSO symmetric mode in the IR (gas) spectrum (1277 cm -1 ) shows a well-defined shoulder at lower wavenumbers (at approximately 1263 cm -1 ) demonstrating the presence of a second conformer, which possesses anticlinal orientation of the N−S bond with respect to the SF 2 group, according to the theoretical calculations.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The characteristic bands centered at 1446 and 1277 cm -1 in the IR spectrum of the gas phase and at 1437 and 1272 cm -1 in the Raman spectrum of the liquid phase are straightforwardly assigned to the antisymmetric and symmetric NSO stretching modes, respectively, in fair agreement with the data reported for the related molecules FSO 2 NS(O)F 2 , NCNS(O)F 2 , and FCONS(O)F 2 . The band assigned to the NSO symmetric mode in the IR (gas) spectrum (1277 cm -1 ) shows a well-defined shoulder at lower wavenumbers (at approximately 1263 cm -1 ) demonstrating the presence of a second conformer, which possesses anticlinal orientation of the N−S bond with respect to the SF 2 group, according to the theoretical calculations.…”
Section: Introductionsupporting
confidence: 87%
“…The observed IR (gas) and Raman (liquid) spectra have been assigned on the basis of their calculated vibrational frequencies and intensities (Table ). Furthermore, characteristic wavenumbers of the NS(O)F 2 moiety in the related molecules FSO 2 NS(O)F 2 , NCNS(O)F 2 , and FCONS(O)F 2 have been taken into account. For assignment of the modes belonging to the SF 5 N group additional calculations (MP2) were performed for SF 5 NCO and SF 5 NSF 2 , for which no experimental data are available.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the conformational flexibility of this compound, Cutín and colleagues [44] carried out a gas electron diffraction experiment. Later, Roland Boese et al [45] used X-ray diffraction with the in situ crystallization method to determine the structure of the related solid-phase compound ((fluoroformyl)imidosulfuryl difluoride, compound 27). It revealed that compound 27 is in the antiperiplanar-synperiplanar conformation.…”
Section: Organosulfur Compoundsmentioning
confidence: 99%
“…Syn implies synperiplanar or synclinal and anti implies antiperiplanar or anticlinal. The crystal structure, a vibrational analysis and quantum chemical calculation of FC(O)NaS(O)F 2 have been reported recently [11]. According to these calculations all four conformers correspond to stable structures with the syn-syn form being lowest in energy (in Ref.…”
Section: Introductionmentioning
confidence: 96%